DETERMINATION OF THE CRYOSCOPIC TEMPERATURE OF A FUNCTIONAL MINCED FISH PRODUCT AND THE AMOUNT OF MOISTURE FROZEN IN IT WHEN IT IS FROZEN - A. H. Nugmanov; N. V. Dolganova; N. V. Yartseva (Современная наука и инновации, 2022)
The lack of animal protein has led to the need to design recipes for semi-finished products with a long shelf life, including frozen functional fish plants, with the maximum possible involvement of various aquaculture raw materials. This minced fish product belongs to a new generation of industrial food products thathave all the main properties for them: a given taste, food balance, directed physiological effects and an acceptable cost.